Associations of polyphenolic compounds consumption and the risk of dyslipidemia in the Siberian population - T. I. Batluk; D. V. Denisova; I. P. Berezovikova; L. V. Sherbakova; S. K. Malyutina; Y. I. Ragino (Российский кардиологический журнал, 2020)
Aim. To identify associations of polyphenols consumption in general, as well as their classes with the risk of dyslipidemia in the population of Novosibirsk aged 45-69.Material and methods. In 2003-2005, in the frames of the HAPIEE international project “Determinants of cardiovascular diseases in Eastern Europe: a multicenter cohort study” the population sample aged 45-69 (9360 people, 4266 men and 5094 women, average age - 57.6 years) was examined in Novosibirsk. For the analysis of nutrition, a Food Frequency Questionnaire (FFQ) was used (141 product names). The content of polyphenolic compounds and their classes was evaluated using the European database Phenol-Explorer 3.6. The eating habits of the population and typically consumed foods were taken into account. The determination of total cholesterol and HDL cholesterol levels were carried out by enzymatic method. Hypercholesterolemia was diagnosed with cholesterol level greater than 5.0 mmol/l (190 mg/dL). Levels of HDL cholesterol <1.0 mmol/l in men and <1.2 mmol/l in women were considered as high-density lipoprotein hypocholesterolemia (hypoHDL-C). The concentration of low-density lipoprotein cholesterol was calculated with the Friedewald formula (1972). HyperLDL-C was diagnosed if level of LDL cholesterol was <3.0 mmol / l.Results. The chance of developing of hypercholesterolemia in the quartile with the highest consumption of “other polyphenols” was 20% less (OR 1.2 confidence interval (CI 1.01-0.14), p = 0.033), phenolic acids by 20% (OR 1.2 (CI 1.01-1.42), p = 0.04) and stilbenes by 37% (OR 1.37 (CI 1.15-1.64), p = 0.001) less than in the quartile of low consumption. The risk of developing hypoHDL-C was lower in the quartile of high polyphenols consumption in general by 18% (OR 1.18 (CI 1.002-1.4), p = 0.051), phenolic acids by 32% (OR 1.32 (CI 1.11-1.57), p = 0.001) and the groups of “other polyphenols” by 20% (OR 1.2 (CI 1.01-1.41), p = 0.04). The chance of hyperLDL-C in the high quartile of consumption of “other polyphenols” decreased by 16% (OR 1.16 (CI 1.002-1.355), p = 0.049) and lignans - by 33% (OR 1.33 (CI 1.14-1, 56), p <0.001) compared with low consumption.Conclusion. Thus, the consumption of polyphenols in general and in classes (phenolic acids, stilbenes, and “other polyphenols”) decreased the risk of dyslipidemia in Siberian population.